Income Inequality in Colombia: Reassessing the Effects of Public Spending and Education Provision - Astorquiza Bustos, Bilver Adrian; Mejía Arango, Daniel (Semestre Económico, 2021)
Income inequality in Colombia showed an average reduction of 9.26 % in the period 2008-2018. However, the Gini coefficient places Colombia as the second most unequal country in Latin America, with public spending on education as a percentage of GDP at 4.5 % (twelfth position), rising unemployment rates and modest secondary education provision. It is imperative to reflect on how resources are distributed and about mechanisms for reducing inequality. We test the hypothesis that spending on education reduces inequality, although not in an efficient way, while increasing provision of education generates differential effects. We estimate a panel data model that corrects for endogeneity for twenty-three departments of Colombia and Bogotá D.C. The results suggest that education spending reduces inequality but is inelastic (Î²= -0.05) and is associated with unproductive spending. In terms of education provision, early years education increases inequality, the secondary reduces inequality, while higher education is almost perfectly inelastic (Î²= -0.004). The strategy for reducing inequality is not a general increase in public spending, but targeted increases and the strengthening of mechanisms for improving provision of education.
Keywords: Inequality; public spending on education; education provision; panel data; Colombia.